Design of a simple monitoring system for large-scale networks (Latin-American Journal of Computing, 2020)
Currently, there are network management tools that try to monitor devices from different manufacturers. However, none of them allow you to automate the monitoring tasks carried out on the network. To tackle this problem, we propose a tailored system that automatically checks the networking devices’ configuration files. In this way, the technicians can spend their time resolving the faults found, resulting in a more efficient use of their workdays. The proposed monitoring system was developed for the WAN of Corporación Nacional de Telecomunicaciones (CNT EP) of Ecuador, in which two forms are used for the automatic analysis of configuration records: 1) by interactive use of commands that can be used in any of the devices, independently of his brand. 2) by using the MIB objects of Cisco, which are most of the network devices. The system was developed using free software and the whole, automatic network monitoring is carried out by our system in 14 hours, which represents a reduction in time of approximately 94%.